When SDN meets C-RAN: A survey exploring multi-point coordination, interference, and performance. (15th July 2020) - Zanferrari Morais, Fernando; André da Costa, Cristiano; Alberti, Antonio Marcos; Bonato Both, Cristiano; da Rosa Righi, Rodrigo
Abstract: The transformation of mobile networks towards fifth generation (5G) is considered an unprecedented revolution when compared to the previous generations, mainly because of the support required for three scenarios: ultra reliable and low latency; high throughput broadband; and massive machine type communication. In this context, the evolution from RAN to C-RAN is a significant contribution to advance the deployment of this new generation. C-RAN concepts bring opportunities like centralized processing, improved interference control, flexible fronthaul networks, and support for ultra-dense heterogeneous radio access networks. SDN emerges as a candidate technology for the development of programmable 5G networks, with centralized orchestration and control/data planes decoupling. In this article, we propose a systematic literature review to cover SDN application in the context of 5G communication and C-RAN. In combination with the concepts as mentioned earlier, the article evaluates coordination and interference management features provided by Coordinated Multi-point and Inter-cell Interference Coordination techniques, besides reviewing fronthaul transport tier capabilities offered by SDN for 5G networks. A careful literature analysis shows that there are no revisions with the same focus as that developed in this survey. As contributions, this article presents a novel taxonomy of SDN technology, enabling C-RAN, as well as trending directions and development opportunities for SDN and C-RAN-based 5G networks.